Environmental Variation Contributes to Head Phenotypes in Workers of Camponotus japonicus (Hymenoptera: Formicidae) - Ruoqing Ma; Liangliang Zhang; Lv Yang; Lingxiao Tang; Xiang Zhang; Cong Wei; Hong He (Ecology and Evolution)
ABSTRACT Integrating color polymorphism with intra‐species morphological traits offers substantial opportunities to study the eco‐evolutionary mechanisms underlying local population responses to heterogeneous and dynamic environments. In this study, we examined the head phenotypic diversity and intraspecific morphological traits of Camponotus japonicus (Mayr, 1866) workers across 22 sites in mainland China, ranging from 24°47′ N to 47°51′ N in latitude and 88°07′ E to 126°43′ E in longitude, covering an altitudinal range up to 1243 m. We classified the head phenotypes of these workers into four types and investigated environmental variables explaining the levels of polymorphism, quantified by the Shannon diversity index and head phenotype ratios. Phylogenetic analysis based on the mitochondrial COI gene classified all samples into four clades. By controlling the genetic distance in our analysis, we revealed the correlations between temperature, precipitation, and the prevalence and distribution of this color polymorphism across the sampled populations. Contrary to the thermal melanism hypothesis, our findings reveal that the prevalence of maroon‐headed workers (lighter coloration) increases with latitude, with the highest proportion of these individuals found in high‐latitude populations (colder, drier regions). Moreover, temperature and precipitation also show significant correlations with the morphological traits of workers, implying that specific traits may be environmentally influenced, potentially contributing to colony‐level survival in fluctuating environments. By emphasizing the often‐overlooked intraspecific variations, our research contributes to understanding how head color polymorphism and intraspecific morphological traits in ants are associated with local population responses to environmental changes.